2014
DOI: 10.1063/1.4902071
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale tunability of solitary wave dynamics in tensegrity metamaterials

Abstract: A new class of strongly nonlinear metamaterials based on tensegrity concepts is proposed and the solitary wave dynamics under impact loading is investigated. Such systems can be tuned into elastic hardening or elastic softening regimes by adjusting local and global prestress. In the softening regime these metamaterials are able to transform initially compression pulse into a solitary rarefaction wave followed by oscillatory tail with progressively decreasing amplitude. Interaction of a compression solitary pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
142
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 152 publications
(149 citation statements)
references
References 19 publications
3
142
0
Order By: Relevance
“…3). While compression solitary waves in uniform granular chains have a constant width, which is independent of the amplitude [29], the width of similar waves in tensegrity metamaterials changes with amplitude and speed, and the solitary wave tends to concentrate on a single lattice spacing in the high energy regime [15,4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3). While compression solitary waves in uniform granular chains have a constant width, which is independent of the amplitude [29], the width of similar waves in tensegrity metamaterials changes with amplitude and speed, and the solitary wave tends to concentrate on a single lattice spacing in the high energy regime [15,4].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that tensegrity lattices exhibit a tunable geometrically nonlinear response, which switches from stiffening to softening by playing with a number of mechanical, geometrical, and prestress variables [1,2,3,4]. Tensegrity lattices consists of networks of prestressable truss structures, obtained by connecting compressive members (bars or struts) through pre-stretched tensile elements (cables or strings).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, physical models of pentamode isolators need to be constructed, employing, e.g., additive manufacturing techniques [8,9], and laboratory tested as seismic base-isolation devices [19], in order to experimentally asses their isolation and dissipation capabilities arising, e.g., from inelastic response and/or material fracture [20]. Another relevant generalization of the present research regards the design of dynamically tunable systems based on the insertion of prestressed cables and/or curved rods within pentamode lattices, with the aim of designing novel metamaterials and bio-inspired lattices tunable by local and global prestress [12][13][14][21][22][23][24][25][26][27][28]. Future studies will also address the experimentation of pentamode materials as components of new-generation seismic dampers.…”
Section: Discussionmentioning
confidence: 99%
“…These may include: exceptional strength-and stiffness-to-weight ratios; excellent strain recoverability; very soft and/or very stiff deformation modes; auxetic behavior; phononic bandgaps; sound control ability; negative effective mass density; negative effective stiffness; negative effective refraction index; superlens behavior; and/or localized confined waves, to name some examples (cf. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] and references therein). The category of "extremal materials" has been introduced in [3] to define materials that simultaneously show very soft and very stiff deformation modes (unimode, bimode, trimode, quadramode and pentamode materials, depending on the number of soft modes).…”
Section: Introductionmentioning
confidence: 99%